2023
DOI: 10.1017/jfm.2023.294
|View full text |Cite
|
Sign up to set email alerts
|

Transient behaviour of decelerating turbulent pipe flows

Abstract: This investigation characterises the time response and the transient turbulence dynamics undergone by rapidly decelerating turbulent pipe flows. A series of direct numerical simulations of decelerating flows between two steady Reynolds numbers were conducted for this purpose. The statistical analyses reveal that rapidly decelerating turbulent flows undergo four coherent, unambiguous transitional stages: inertial (stage I), a dramatic change of sign in the viscous force associated with the decay of the viscous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Transition between laminar and turbulent unsteady flow is still, despite its importance in many engineering applications, not fully understood [ 162 ]. Recently, Guerrero et al reviewed the literature and performed DNS to investigate the transient behavior of accelerating [ 163 ] and decelerating [ 164 ] turbulent pipe flows. An early discussion of the transition between laminar and turbulent flow in pulsatile flow in the cardiovascular system was published by Yellin [ 165 ], who observed that large instantaneous Reynolds numbers did not result in transition to turbulence everywhere.…”
Section: Part I—computational Rhinologymentioning
confidence: 99%
“…Transition between laminar and turbulent unsteady flow is still, despite its importance in many engineering applications, not fully understood [ 162 ]. Recently, Guerrero et al reviewed the literature and performed DNS to investigate the transient behavior of accelerating [ 163 ] and decelerating [ 164 ] turbulent pipe flows. An early discussion of the transition between laminar and turbulent flow in pulsatile flow in the cardiovascular system was published by Yellin [ 165 ], who observed that large instantaneous Reynolds numbers did not result in transition to turbulence everywhere.…”
Section: Part I—computational Rhinologymentioning
confidence: 99%
“…Turbulent kinetic energy is the most common physical quantity used to describe the degree of fluid turbulence pulsation. It can be used to measure the fluid viscous dissipation loss and the range of pulsation diffusion [19]. Fig.…”
Section: Analysis Of Transient Turbulent Kinetic Energy and Vorticity...mentioning
confidence: 99%
“…Guerrero et al [86] investigated the turbulence flow dynamics and time response experienced by sudden decelerating turbulent flow through pipes using direct numerical simulation data sets of linearly decelerated turbulent pipe flows. The turbulence response of a fully developed turbulent flow exhibits a phase lag when the flow is subjected to linear acceleration.…”
Section: Decelerating Flowsmentioning
confidence: 99%
“…(v) Meanwhile, the near-wall region displays a stationary mean velocity profile. Figure 15a shows a ramp down in flow rate was enforced at t +1 = 0 to rapidly reduce the Reynolds number and Figure 15b depicts that the time response of the skin friction coefficient indicates that flow undergoes several transient behaviours before becoming stationary [86].…”
Section: Decelerating Flowsmentioning
confidence: 99%